2021
DOI: 10.18203/issn.2454-2156.intjscirep20211453
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of skin diseases among patients attending Hawassa university comprehensive specialized hospital, Hawassa, Ethiopia

Abstract: <p><strong>Background</strong>: Spectrum of skin diseases varies from region to region due to several factors such as genetics, socioeconomic and environmental. This study aimed to determine the pattern of various skin disorders appearing in the dermatology department of a tertiary care hospital.</p><p><strong>Methods</strong>: All patients attending the dermatology clinic of the Hawassa university comprehensive specialized hospital, from January 2017 to December 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…This finding is consistent with xiao et al, who reported urticaria in 2.7% and Aassefa et al who reported a rate of 3.1% . [48,49] However, the figure is lower than noted in Pakistani 10 % [10].The low figure in our study may be due to like hood of most the patients to present to the emergency and medical OPD rather than the skin clinic. Papular urticaria (insect bite reaction) accounting for 1.6 % of all cases.…”
Section: Discussioncontrasting
confidence: 71%
“…This finding is consistent with xiao et al, who reported urticaria in 2.7% and Aassefa et al who reported a rate of 3.1% . [48,49] However, the figure is lower than noted in Pakistani 10 % [10].The low figure in our study may be due to like hood of most the patients to present to the emergency and medical OPD rather than the skin clinic. Papular urticaria (insect bite reaction) accounting for 1.6 % of all cases.…”
Section: Discussioncontrasting
confidence: 71%